PIROLISIS PELEPAH KELAPA SAWIT UNTUK MENGHASILKAN FENOL PADA ASAP CAIR - Seri Maulina; Nurtahara; Fakhradila (Jurnal Teknik Kimia USU, 2018)
Palm midrib is a waste in oil palm plantations that containing cellulose, hemicellulose and lignin compounds. Palm midrib pyrolysis will produce phenol derived from lignin. The purpose of this study was to obtain phenol compounds as a function of time and temperature. The pyrolysis process was carried out at 200 °C, 300 °C, 400 °C, 500 °C and 600 °C with variation of pyrolysis time of 30 minutes, 60 minutes and 90 minutes. The analysis was performed using UV-Visible Spectrophotometer. The content of phenol compounds in liquid smoke increases with the rise of temperature and pyrolysis time. The highest total phenol content in liquid smoke was obtained at 600 °C for 90 minutes pyrolysis, which was 17.966%.